Philippine High-School Teachers' Cognition of Pronunciation Teaching - Santillan, Jennifer; Balinas, Elvira; Couper, Graeme (Jilin University, 2023)
This study contributes to the steadily developing global picture of teacher cognition of pronunciation teaching by presenting the perspective of the Philippine context. It surveyed teachers’ knowledge, attitudes, beliefs, and practices, as well as the impact of Covid-19 on pronunciation teaching and learning. The 251 responses from junior and senior high school English teachers suggest that pronunciation teaching in the Philippines is in a relatively healthy state. Teacher education appears to prepare teachers well, especially in terms of knowledge of phonetics and phonology and confidence in their own pronunciation. Although there was learning on how to teach pronunciation, respondents indicated that more was needed. Teachers wanted their students to communicate effectively rather than have native-like accents, and most notably, intonation teaching was high on the priority list. Additionally, distance learning during Covid-19 often meant that pronunciation was neglected. The study identifies a number of areas for follow-up in-depth qualitative studies.
Keywords: General Science & Technology